Stars over Alaska - Snow, Jennifer (Snow, Jennifer. Wild River, 2021)
Agent Leslie Sanders returns to Wild River, Alaska to wait out the search for the stalker of her client, a young Hollywood star. Leslie believed she was moving on with her life in LA, but she's still not over the death of her fiancé, and seeing Levi Grayson makes everything that much harder. Levi is in Alaska's elite group of wildland firefighters. When Leslie left Wild River after Dawson's death, it hurt Levi to lose his two best friends in a matter of weeks. Resisting his feelings for Leslie when Dawson was alive was tough, but Levi isn't sure he's strong enough anymore to fight the attraction between them. The book includes the bonus story "A Wild River Match" by Jennifer Snow.